Making out in Japanese - Geers, Todd; Hoburg, Erika (Tuttle Publishing, 2014)
The books in the Making Out series are fun and accessible guides to languages as they're spoken on the street. These classic phrase books have been updated and expanded for use in informal situations such as bars, parties, or anywhere else one needs to know slang to survive! The books also now feature phrases written in their native script as well as in English, so the book can be shown to the person you are trying to communicate with. With transcriptions revised for easier pronunciation, these helpful books will have you making out in no time!Making Out in Japanese is a fun, accessible and th.